Associations between depressive symptoms and being employed or retired in older adults with type 2 diabetes - Brandão, Maria Piedade (A pilot randomized controlled trial examining the feasibility, acceptability, and efficacy of Adapted Motivational Interviewing for post-operative bariatric surgery patients, 2020)
• The subpopulation of older Europeans with type 2 diabetes was studied. • The majority of patients with depression were women. • Patients with depression had lower employment rates. • Women employed were more likely to have depression than the ones retired. • Improvement of psychosocial working conditions is needed.